The Role of Digital Learning Objects in Personalized Education - Bungai, Joni; Permana, Indra; Anis, Nina; Zaman, Khalil (Journal International Inspire Education Technology, 2024)
Digital Learning Objects (DLOs) have emerged as key tools in promoting personalized education, offering students flexible, adaptable resources that can be tailored to individual learning styles, preferences, and paces. With increasing demand for personalized learning experiences, DLOs provide an innovative approach to meet diverse educational needs by allowing educators to create and deploy interactive, multimedia-rich content. This research aims to explore the effectiveness of DLOs in enhancing personalized education in secondary school settings, examining their impact on student engagement, comprehension, and learning outcomes. A mixed-methods approach was employed, combining quantitative analysis of student performance data with qualitative feedback from students and educators. Data were collected from two groups: one group utilizing DLO-based lessons and a control group following traditional instructional methods. Surveys, interviews, and assessment scores were analyzed to determine the effect of DLOs on individualized learning experiences and overall academic success. The findings reveal that students in the DLO group demonstrated improved engagement and a 20% higher retention rate compared to the control group, with educators noting greater adaptability to varying skill levels and learning preferences. Students reported feeling more in control of their learning, highlighting DLOs’ potential in promoting autonomy and motivation. This study concludes that DLOs are effective tools for supporting personalized education, helping educators cater to individual learning needs. Future research is recommended to explore long-term impacts of DLO integration and its effectiveness across different educational contexts.